Differentiated Assessment in Negotiation Text Instruction: A Qualitative Study in Indonesian Senior Secondary Education - Atika Zikri; Amril Amir; Abdurahman Abdurahman (JF Publisher, 2026)
The integration of differentiated assessment into subject-specific language instruction remains empirically underdeveloped, particularly within the Indonesian senior secondary context shaped by Kurikulum Merdeka. This study aimed to describe the implementation of differentiated learning assessment across the content, process, and product components of negotiation text instruction at the senior secondary level. A qualitative descriptive design was employed, with an Indonesian language teacher at SMAN 1 Sumatera Barat serving as the primary informant. Data were collected through a structured questionnaire and a semi-structured interview, then analyzed using the Miles, Huberman, and Saldana (2014) framework of data reduction, data display, and conclusion drawing. Trustworthiness was ensured through instrument triangulation, member checking, and peer debriefing. The findings indicate that differentiated assessment was implemented effectively across all three components. Content differentiation was achieved through varied material formats and complexity levels responsive to students' readiness and learning profiles. Process differentiation was realized through negotiation simulation, group discussion, and multimedia presentation activities that promoted active and equitable participation. Product differentiation afforded students meaningful choice in demonstrating learning outcomes, enabling assessment that served both summative and formative functions. Key implementation constraints included time limitations, heterogeneous group management, and inconsistent student self-directedness. The findings offer subject-specific empirical guidance for Indonesian language teachers designing differentiated assessment practices aligned with the principles of Kurikulum Merdeka.